Piriformospora indica and its related species Sebacina vermifera promote growth and development and phosphorus nutrition in tomato - WANG Feng-rang; MAO Ke-ke; LI Guo-jun; WU Cheng-cheng; ZHANG Hui-juan; LI Da-yong; SONG Feng-ming (浙江大学学报. 农业与生命科学版)
The colonization of Piriformospora indica and Sebacina vermifera in roots of tomato plants was examined and their effects on growth and development of tomato plants were studied under normal and phosphorus deficit stress conditions. The results showed that both P. indica and S. vermifera could colonize the epidermal and root hair cells of tomato roots. The colonization of P. indica and S. vermifera promoted vegetable growth and fruit development and increased lateral roots of tomato plants. P. indica and S. vermifera facilitated Pi uptake and increased total Pi contents in tomato plants under normal and low Pi conditions, and improved growth performance of tomato plants under low Pi condition. It is indicated that both P. indica and S. vermifera can be developed to improve growth and development as well as Pi nutrition in crop plants.